Second Five Year Plan Bombay State District Ahmednagar - Government of Bombay (Government of Bombay, 1958)
The Second Five-Year Plan (1956–61) for Ahmednagar District presents a comprehensive strategy for socio-economic development, emphasizing agriculture, irrigation, education, health, land reforms, industry, and infrastructure. Agricultural initiatives focus on increasing productivity through improved seeds, fertilizers, irrigation schemes, and modern cultivation methods, with particular attention to crops such as Jowar, Bajri, Wheat, Sugarcane, and Cotton. Major irrigation projects, including the Bhandardara Dam on the Pravara River and new schemes on the Mula and Ghod rivers, aim to expand cultivable land and reduce dependence on rainfall. Land reforms under the Bombay Tenancy and Agricultural Lands Act, 1955, target redistribution to tenants and consolidation of fragmented holdings to enhance productivity. Education receives priority through the expansion of primary, secondary, higher, technical, and vocational institutions, teacher training programs, and adult literacy campaigns, complemented by physical and social education initiatives. Health improvements include mobile dispensaries, disease prevention campaigns, and the establishment of primary health units. Industrial and rural development emphasize cottage and small-scale industries, cooperative societies, and participation in sugar factories and grain banks to uplift artisans and backward classes. Infrastructure development, including road construction and connectivity improvements, facilitates trade, market access, and integration of rural communities. Complementary social welfare measures focus on women, children, and marginalized groups, fostering community engagement and local governance through panchayats. Collectively, the plan articulates a structured and inclusive roadmap aimed at sustainable growth, improved living standards, and the socio-economic empowerment of Ahmednagar District.
District Ahmednagar
District Ahmednagar
Keywords: Second Five-Year Plan; Ahmednagar District; Agricultural Development; Irrigation Projects; Land Reforms; Education Expansion; Health Services; Industrial Cooperatives; Rural Infrastructure; Cottage Industries; Community Participation; Social Welfare